The Impact Of Foreign Directors, Returnee Directors And Foreign Ownership On Corporate Innovation In Chinese Listed Manufacturing Companies - Pu, Tingqian (2024)
Economic globalization has driven the unprecedented worldwide integration of talent, capital, and other productive factors, offering emerging market enterprises new opportunities for innovation. Against the backdrop of corporate innovation becoming a crucial strategy for achieving superior performance and maintaining competitive advantage, research on how foreign directors, returnee directors, and foreign ownership affect corporate innovation remains limited. Using a sample of 17980 firm-year observations in the Chinese listed manufacturing companies during 2008–2021, this study evaluates the relationships between foreign directors, returning directors, foreign ownership, and corporate innovation from a corporate governance perspective. Additionally, this study examines the interaction effect of state ownership on the relationship between returnee directors and corporate innovation. Unlike previous research designs, this study categorizes foreign directors and returnee directors into three distinct types each and foreign ownership into two types. The findings indicate that foreign independent directors, foreign chairmen, returnee directors with overseas study background, returnee directors with overseas work background, and returnee directors with dual backgrounds positively and significantly affect corporate innovation.